Statistical experimental study for verifying thermal characteristics of insulated double pipe - Lee, Jae Hoon; Yoon, Jeong Hwan; Kim, Si Pom (Journal of mechanical science and technology, 2018)
This study investigates the heat transfer characteristics of an insulated double pipe in accordance with the degree of vacuum and the working fluid pressure for liquefied natural gas transportation. A total of 16 cases were examined, and the degree of vacuum was set at 760, 0.1, 0.01 and 0.001 torr. Meanwhile, the working fluid pressure was set at 1, 3, 5 and 7 bar to analyze the effect of variables. A correlation analysis based on statistics was performed to quantitatively study the temperature distribution and the heat transfer characteristics. An approximated formula on the quantity of heat depending on the thermal conductivity of rarefied gas was also calculated. The approximated curve was compared with the theory formula. Consequently, the heat insulation property was improved in proportion to the degree of vacuum. A comparison of the approximated curve and the theory formula further showed that thermal conductivity was dominant at a high degree of vacuum.